Iron overload in patients with transfusion dependent myelodysplastic syndrome - Genadieva Stavrikj, Sonja; Georgievski, Borche; Stojanoski, Zlate; Krstevska Balkanov, Svetlana; Pivkova Veljanovska, Aleksandra; Trajkovska, Meri; Genadieva Dimitrova, Magdalena; Serafimoski Vladimir (Македонска академија на науките и уметностите, Одделение за биолошки и медицински науки = Macedonian Academy of Sciences and Arts, Section of Biological and Medical Sciences, 2011)
The myelodisplastic syndrome is a heterogeneous group of diseases, characterised by ineffective and dysplastic haematopoesis and pancytopenia in the peripheral blood, followed by progressive disturbance of differentiation of the haematopoetic stem cell, resulting in evolution of the disease towards acute leukaemia. According to the latest WHO classification, the term myelodisplastic syndrome includes diseases with an indolent course, as well as diseases with a fast evolution towards acute leukaemia. Because of this diversity, haematologists base their therapeutic decisions on prognostic scoring systems which incorporate all the significant factors with an influence on survival in this group of patients with myelodisplastic syndrome. Bearing in mind that anaemia is the most frequent form of cytopenia in patients with myelodisplastic syndrome, it is common that at some point of the disease almost every patient with myelodisplastic syndrome is transfusion-dependent. Frequently applied transfusions secure the correction of anaemia in these patients, giving them a good quality of life, but at the same time endangering them with the potential threat of iron overload, when the physiological mechanisms of iron excretion from the organism become insufficient. There is a clear correlation between transfusion dependence and the overall survival in patients with myelodisplastic syndrome. Chelators secure the lowering of the iron surfeit and are indicated in transfusion-dependant patients with myelodisplastic syndrome ( need for two blood units monthly, during one year ), when the ferritin level increases over 1000, in patients who are candidates for transplantation as well as in patients from good prognostic groups with median survival over one year. The therapy with chelators lasts as long as the patient is transfusion-dependant. Key words: myelodisplastic syndrome, chelators, iron overload
Keywords: myelodysplastic syndromes; iron overload